(untitled) (Malaysian Journal of Civil Engineering, 2018)
The performance of a simple model with a linear root water extraction term that varies with time is presented in this paper. The research is based on the use of a one-dimensional form of Richard’s Equation for unsaturated moisture flow including a sink term. A numerical solution has been achieved via the finite element method for spatial discretisation along with a finite difference time-marching scheme. The model is assessed via a series of simulations of water uptake beneath uniform crop cover. A good correlation between the field data and simulated results has been achieved. This relatively straight forward approach is seemed more suitable for development and application to a range of geoengineering problems such as slope stability, shrinkage and heave prediction.